2018
DOI: 10.2147/ndt.s137776
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalogram alpha asymmetry in patients with depressive disorders: current perspectives

Abstract: PurposeElectroencephalogram (EEG) alpha asymmetry (AA) in depressive disorders has been of interest over the last few decades, but it continues to remain unclear whether EEG AA can discriminate between healthy and depressive individuals.Materials and methodsA systematic literature search for papers addressing EEG AA using the keywords alpha asymmetry, depression, and EEG was performed in PubMed. All studies were checked for sample size, gender, handedness, reference, recording protocol, EEG band range, impedan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 84 publications
(98 reference statements)
4
34
0
1
Order By: Relevance
“…Deviated EEG activity in the alpha frequency is one of the most frequently reported aberrations of the EEG signal in a wide range of diseases [ 35 , 36 , 37 ]. Alpha oscillations predominantly originate from the occipital lobe during wakeful relaxation with closed eyes in healthy people, but according to Novikova [ 38 ], individuals of varying degrees of blindness display a correlation between the alpha reduction and the remaining visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…Deviated EEG activity in the alpha frequency is one of the most frequently reported aberrations of the EEG signal in a wide range of diseases [ 35 , 36 , 37 ]. Alpha oscillations predominantly originate from the occipital lobe during wakeful relaxation with closed eyes in healthy people, but according to Novikova [ 38 ], individuals of varying degrees of blindness display a correlation between the alpha reduction and the remaining visual acuity.…”
Section: Discussionmentioning
confidence: 99%
“…EEG resting state studies have demonstrated differences between participants with MDD and healthy controls (5, 7, 18, 6769), among them decreased selectivity of functional connectivity during the resting state in MDD, and some with a particular emphasis on the theta and alpha frequency bands (1920, 21, 70).…”
Section: Discussionmentioning
confidence: 99%
“…Other resting state studies, however, have found greater functional connectivity in the theta and alpha bands in MDD when compared with healthy controls (18) as well as a decrease in long-range temporal correlations (19). A recent review found that studies of alpha asymmetry in MDD patients had inconsistent findings (20), despite its early promise (21).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, despite the tremendous progress in computing power and available algorithms, the spectral band approach continues to persist as the dominant approach to EEG analysis, including in the development of clinical biomarkers. A recent example of this is the approval by the FDA 4 of the use of the theta/beta ratio as a biomarker for ADHD diagnosis (Saad et al, 2015; Gloss et al, 2016) whilst others are exploring the application of alpha-asymmetry as a potential marker for depression (van der Vinne et al, 2017; Kaiser et al, 2018). One question, therefore, is whether the approach of splicing the power spectrum into bands has persisted because it offers a superior approach in terms of research insight, methodological standardization, and reliability of results across studies, or whether it is because researchers have simply kept with the status quo of 80 years ago.…”
Section: Introductionmentioning
confidence: 99%